A Matched Comparison of the Long-Term Outcomes of Cemented and Cementless Total Knee Replacements: An Analysis from the National Joint Registry of England, Wales, Northern Ireland and the Isle of Man. (15th December 2021) - Mohammad, Hasan R.; Judge, Andrew; Murray, David W.
Abstract : Background: Total knee replacements (TKRs) can be implanted with or without the use of cement. It is currently uncertain how cemented and cementless TKRs compare overall and in different age groups of the population in the long term. Methods: The National Joint Registry collects information on knee replacements inserted in England, Wales, Northern Ireland, and the Isle of Man and was linked for multiple confounders to the National Health Service Hospital Episode Statistics database. With use of propensity score matching techniques, 44, 954 cemented and cementless TKRs were compared. Regression models were used to compare the outcomes of revision, reoperation, and mortality both overall and in different age strata. Results: The 10-year implant survival rate with revision as the end point for cemented and cementless TKRs was 96.0% and 95.5%, respectively (hazard ratio [HR] = 1.14; p = 0.01). The 10-year survival rate with reoperation as the end point was 82.7% and 81.4%, respectively (HR = 1.08; p = 0.001). The rate of revision for pain was higher for cementless TKRs (0.5% [cemented] compared with 0.7% [cementless]; p = 0.002), but the rate of revision for infection was lower (0.7% [cemented] compared with 0.5% [cementless]; p = 0.003). No significant interactions with age existed for the outcomes of revision (p = 0.24), reoperation (p = 0.30), or mortality (p = 0.58). Conclusions: We found that matched cemented and cementless TKRs both have 10-year implant survival rates of >95%. Cementless TKRs had a higher revision rate (absolute difference, 0.5%) and reoperation rate (absolute difference, 1.3%). The rate of revision for infection was lower in the cementless group, although the rate of revision for pain was higher. Age did not significantly affect the relative performances. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.